STRATEGI GURU PAI DALAM MENINGKATKAN HAFALAN AL-QUR’AN PESERTA DIDIK - Afi Mika Nada Kamelia; Mohammad Zakki Azani (PAI RAFAH, 2023)
SMP Muhammadiyah 8 Kebakkramat is an Islamic school that guides its students to memorize the Qur'an. Memorizing the Qur'an is done to increase students' love and closeness to the Qur'an and to achieve the virtues of memorizing the Qur'an. To improve the memorization ability of students at SMP Muhammadiyah 8 Kebakkramat, PAI teachers have various efforts including providing motivation to students to have enthusiasm and sincerity in memorizing the Qur'an, memorizing the Qur'an in class, repeating memorization or muroja'ah, collaborating with parents or guardians of students, flash pesantren, and conducting evaluations to determine whether or not there is an increase in students in memorizing the Qur'an. This research was conducted to find out and describe the PAI teacher's strategy in improving students' ability to memorize the Qur'an at SMP Muhammadiyah 8 Kebakkramat. This research uses qualitative research methods, which seek information about existing symptoms, determine the objectives to be achieved clearly, plan procedures and collect data for reporting. Interviews were conducted with PAI teachers to obtain information about the ways to improve student memorization and the practices carried out. The results showed that PAI teachers have several strategies, namely by providing motivation to students, memorizing the Qur'an in class using several methods.